Identifying Service Market Reform Priorities in Italy - Belhocine, Nazim (IMF Working Papers; Working Paper ;, 2020)
Italy's labor productivity in market services has declined since 2000, underperforming manufacturing and peer European countries, especially in strongly regulated sectors. A model of monopolistic competition is used to identify which service sectors would benefit more from removing entry and/or exit barriers. Using Italian firm-level data, the paper finds that sectors with high markups, such as professional services, would primarily benefit from removing entry barriers. Sectors with a large mass of unproductive firms, such as retail, would instead benefit from removing exit barriers. Policy recommendations to improve efficiency are outlined in relation to the sectoral priorities identified in the data.